Socio-Cultural and Linguistic Behavior of Arabic-Speaking Students: Fake Identity Among Internet Users and Its Effects/ السلوك الاجتماعي والثقافي واللغوي للطلاب الناطقين باللغة العربية: الهوية المزيفة بين مستخدمي الإنترنت وآثارها - Khalid Hassan Alabri (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This research aims to discuss the use of anonymous and fake names instead of real names, the hiding of internet users' real identities, and the adverse effects of such disguise. This study follows a descriptive method, in which information is gathered through the author's observations. The goal is to understand the key reasons for using a fictitious persona on the internet by describing the phenomenon and collecting descriptions/information about it. The paper will also extrapolate and track the conditions of internet users through review and observation. Findings: Hiding an identity allows a person to do/say what they could not in their real name. This can result in behaviors that are destructive to society, such as showing bad morals, spying on others, a weak family bond, violation of privacy/security, and promoting terrorism. The scientific value of this paper is its discussion of such a sensitive topic as hiding one’s identity, and the consequences of being anonymous on the internet. The paper did not address the reasons for hiding one’s identity, as that discussion was beyond its scope. Instead, the study discusses treatment for this trend, whether it affects the anonymous person or others who suffer consequences. Such consequences affect various aspects of life, such as religious, social, moral, and even security. This research benefits Arabic language teaching by laying a foundation in grammatical and linguistic terminology, thereby contributing to the explanation of terms such as nouns, nicknames, and titles. Furthermore, it enhances critical thinking and linguistic analysis skills, helping teachers teach